Pancrustacean phylogeny: hexapods are terrestrial crustaceans and maxillopods are not monophyletic - Regier, Jerome C. (The Royal Society, 2005)
Recent molecular analyses indicate that crustaceans and hexapods form a clade (Pancrustacea or Tetraconata), but relationships among its constituent lineages, including monophyly of crustaceans, are controversial. Our phylogenetic analysis of three protein-coding nuclear genes from 62 arthropods and lobopods (Onychophora and Tardigrada) demonstrates that Hexapoda is most closely related to the crustaceans Branchiopoda (fairy shrimp, water fleas, etc.) and Cephalocarida+Remipedia, thereby making hexapods terrestrial crustaceans and the traditionally defined Crustacea paraphyletic. Additional findings are that Malacostraca (crabs, isopods, etc.) unites with Cirripedia (barnacles, etc.) and they, in turn, with Copepoda, making the traditional crustacean class Maxillopoda paraphyletic. Ostracoda (seed shrimp)—either all or a subgroup—is associated with Branchiura (fish lice) and likely to be basal to all other pancrustaceans. A Bayesian statistical (non-clock) estimate of divergence times suggests a Precambrian origin for Pancrustacea (600 Myr ago or more), which precedes the first unambiguous arthropod fossils by over 60 Myr.